Identifying the Loyalty of Generation Z K-Pop Fans by Utilizing Regional Creative Economy Talents to Support Regional Culture - Canon, Lidya Djuwita Pratiwi; Wua, Injilia Wulan Gratia (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The K-Pop phenomenon as part of global popular culture has influenced the lifestyle of Generation Z in Indonesia, especially in aspects of media consumption, community participation, and consumer behavior towards Korean-themed products. This study aims to identify the loyalty of Generation Z K-Pop fans and explore the potential for utilizing regional creative economy talents to support local cultural promotion. The research method used a mixed methods approach with a quantitative survey of 100 Generation Z respondents and qualitative analysis through interviews, observations, and Focus Group Discussions (FGDs). Quantitative data were analyzed using multiple linear regression, while qualitative data were analyzed using NVivo software. The results show that K-Pop fan loyalty and regional creative economy talents have a significant influence, both simultaneously and partially, on regional culture. Thematic analysis shows that K-Pop fandom can be an entry point for introducing local creative products and making regional culture more relevant among the younger generation. Thus, this study concludes that Generation Z K-Pop fan loyalty can be utilized as an innovative and sustainable collaborative strategy in supporting regional cultural promotion by strengthening local creative economy talents.